2016
DOI: 10.4102/sajems.v19i3.1397
|View full text |Cite
|
Sign up to set email alerts
|

Art investment in South Africa: Portfolio diversification and art market efficiency

Abstract: Art has been suggested as a good way to diversify investment portfolios during times of financial uncertainty. The argument is that art exhibits different risk and return characteristics to conventional investments in other asset classes. The new Citadel art price index offered the opportunity to test this theory in the South African context. Moreover, this paper tests whether art prices are efficient. The Citadel index uses the hedonic regression method with observations drawn from the top 100, 50 and 20 arti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Upton-Hansen, 2018), and indeed existing research has evidenced the direct link between the two. In separate analyses, Goetzmann et al (2011) and Botha et al (2016) for example found a positive lagged relationship between stock-market performance and art price indexes. Consequently, noting the highly unequal participation in stock-market gains, art prices have been found to be widely impacted by economic inequality:…”
Section: The Rise Of Inequality and The Impact On Artistic Critiquementioning
confidence: 95%
See 1 more Smart Citation
“…Upton-Hansen, 2018), and indeed existing research has evidenced the direct link between the two. In separate analyses, Goetzmann et al (2011) and Botha et al (2016) for example found a positive lagged relationship between stock-market performance and art price indexes. Consequently, noting the highly unequal participation in stock-market gains, art prices have been found to be widely impacted by economic inequality:…”
Section: The Rise Of Inequality and The Impact On Artistic Critiquementioning
confidence: 95%
“…Upton-Hansen, 2018), and indeed existing research has evidenced the direct link between the two. In separate analyses, Goetzmann et al (2011) and Botha et al (2016) for example found a positive lagged relationship between stock-market performance and art price indexes. Consequently, noting the highly unequal participation in stock-market gains, art prices have been found to be widely impacted by economic inequality:[B]uilding a regression on the income tax data of Atkinson and Piketty (2010), [researchers] show that ‘art prices rise when income inequality goes up’, with robust conclusions that a one percent increase in the share of total income earned by the top 0.1 percent triggers an increase in art prices of about 14 percent.…”
Section: Aesthetic Critique In the Era Of Financialisation And The Rise Of The Super Wealthymentioning
confidence: 95%
“…For example, in the academic literature, the search for an inefficiency market and ways to exploit it has mainly been examined in stock markets (Fama, 1970; Urquhart & McGroarty, 2016), bond markets (Hotchkiss & Ronen, 2002; Zunino et al, 2012), the exchange rate (Taylor & Sarno, 2004) and CDS markets (Kiesel et al, 2016). The theory of price efficiency has also been studied in commodity markets (Charles & Darné, 2009; Kristoufek & Vosvrda, 2014; Smith, 2002) and alternative markets such as art (Aye et al, 2017; Botha et al, 2016; Goetzmann, 1995; Munteanu & Pece, 2015), real estate (Crockett, 1982; Darrat & Glascock, 1993; Gatzlaff & Tirtiroglu, 1995; Clayton, 1998; Kleiman et al, 2002) and bitcoin (Wu & Pandey, 2014; Urquhart, 2016; Kristoufek, 2018; Vidal‐Tomás & Ibañez, 2018; Wei, 2018; Jena et al, 2020).…”
Section: Introductionmentioning
confidence: 99%